The Effectiveness of Resilience-Based Group Training on Uncertainty Intolerance, Future Orientation, and Stress Appraisal in High School Students - Soleimanipour, Manizheh (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective: The present study aimed to investigate the effectiveness of resilience-based group training on intolerance of uncertainty, future orientation, and stress appraisal among high school students.Methods and Materials: The present study employed a quasi-experimental design with a pretest-posttest structure and a control group. The statistical population consisted of high school students in Ahwaz during the 2025–2026 academic year. Using multistage cluster sampling, 40 students were selected and randomly assigned to an experimental group (n = 20) and a control group (n = 20). Data collection instruments included the Intolerance of Uncertainty Scale developed by Freeston et al., the Future Orientation Questionnaire developed by Seginer, and the Stress Appraisal Measure developed by Peacock and Wong. The experimental group participated in eight 90-minute sessions of resilience-based group training, while the control group received no intervention during the study period. Data were analyzed using descriptive statistics and multivariate analysis of covariance (MANCOVA) in IBM SPSS Statistics version 27.Findings: The results of multivariate analysis of covariance revealed a statistically significant overall effect of resilience-based group training on the combined dependent variables of intolerance of uncertainty, future orientation, and stress appraisal (Wilks’ Lambda = 0.29, F = 28.94, p < .001, η² = 0.71). Univariate analyses further indicated that the intervention significantly reduced intolerance of uncertainty (F = 41.28, p < .001, η² = 0.53) and maladaptive stress appraisal (F = 44.36, p < .001, η² = 0.56), while significantly increasing future orientation among students in the experimental group compared with the control group (F = 46.91, p < .001, η² = 0.57). The obtained effect sizes demonstrated that the resilience-based intervention exerted substantial positive effects on students’ adaptive psychological functioning.Conclusion: The findings of the present study suggest that resilience-based group training is an effective psychological intervention for reducing intolerance of uncertainty and maladaptive stress appraisal while enhancing future orientation among high school students. Strengthening resilience-related capacities may improve adolescents’ emotional adjustment, coping flexibility, and positive future-directed thinking.